Seminar Eksplorasi Etnomatematika pada Tari Losuong Khas Kampar - Zulfah, Zulfah; Ulfainsani, Sri; Rahayu Putri, Elsi; Susanti, Risma; Nur Syafitri, Citra; Novelena, Dwi; Nasrulloh, Imam (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The purpose of this study was to disseminate the results of the Ethnomatematics Exploration on the Kampar Typical Losuong Dance. Losuong dance is one of the typical dances of Kampar. The Losuong dance is a community dance when welcoming the celebration of the rice harvest festival as a form of community gratitude for the blessings of the harvest given by God Almighty. Nowadays, the Losuong Dance is also performed at carnivals and cultural parades, weddings, commemorations of the sinking of the Old Village, Koto Panjang, as a welcoming dance for the arrival of important people, and the opening dance for big events. The research shows that ethnomathematics findings were obtained on the movements, properties, and accompaniment of the Losuong Dance, namely the concept of flat shapes, angles, sets and geometric transformations. In addition, this research can be useful for teachers to reference teaching materials in learning mathematics and to gain students' knowledge about the mathematical concepts in Losuong Dance and can be used as a new reference for future researchers.